A new interactive guiding system with social networking services at exhibitions. Issue 2 (1st April 2014) - Lin, Hsien-Tang; W. Lan, Lawrence
Abstract : Purpose: – The purpose of this paper was to develop a new interactive guiding system allowing people to use their own smart mobile devices, such as smart phones or tablet PCs, to activate the guiding services at the art gallery. The system provided interactions between visitors and exhibit items. It focused on the highly interactive functions between visitors and artworks authors as well as among visitors at both exhibition sites and social network sites (SNSs). Design/methodology/approach: – The system used quick response (QR) codes as the context aware elements, Facebook as the platform of SNSs, and smart mobile devices as the human-machine interfaces. Visitors carrying their own smart phones or tablet PCs can activate the guiding services by scanning the QR codes of the interested exhibit items. A system usability scale (SUS) survey was conducted to understand the visitors' perceptions on system usability. A questionnaire survey was conducted to collect the visitors' and authors' attitudes on releasing messages through Facebook. Findings: – The system was implemented at an art centre where lacquer artworks were on display. The SUS survey showed that 94 per cent of the participated visitors have satisfactorily rated this new guiding system, indicating rather high usability of the system. Most participated visitors agreed on Facebook as an ideal channel to release messages and they would pay more attention to the highly-recommended exhibit items. All the artworks authors consented to this new guiding system with potential power to disseminate their works over the cyberspace. Originality/value: – This new system possesses some important features in blending real world and cyberspace activities. Visitors at exhibit sites can become more informed and captivated because the interactive guiding system enables them to share knowledge and commentary opinions with others who were, are or will be at the same exhibition. It also allows people to share with their cyberspace friends who may have no times or opportunities to visit the exhibition. Most importantly, the new system may immensely expand the number of potential visitors in ways to make the authors and their artworks rapidly recognized.